An Estimated Bayesian DSGE Model for Kazakhstan - Abilov, Nurdaulet (Asian Journal of Economic Modelling, 2020)
A small scale open economy model is estimated for Kazakhstan via Bayesian methods. The model explicitly takes into account the dependence of the economy on commodity exports and also accounts for risk premium shocks in the foreign exchange market. The main contribution of the research is that it is the first DSGE model in literature estimated via Bayesian methods for Kazakhstan. The results of the model are used to determine the historical contribution of structural shocks to endogenous variables, forecast error variance decomposition of observed macroeconomic variables and impulse responses of important endogenous variables to various shocks. It has been found that the output gap turned significantly negative during the Great Recession and the negative oil price shock. The effect of contractionary monetary policy is found to be negative on output gap, but it negligibly affects the inflation rate in the economy. Risk premium shocks are found to account for almost 60% of forecast error variance decomposition of nominal exchange rate of tenge over all horizons.